2011
DOI: 10.1039/c0cc05308b
|View full text |Cite
|
Sign up to set email alerts
|

Guiding the nitrogen nucleophile to the middle: palladium-catalyzed decarboxylative cyclopropanation of 2-alkylidenetrimethylene carbonates with isocyanates

Abstract: A palladium-catalyzed decarboxylative cyclopropanation of 2-alkylidenetrimethylene carbonates with isocyanates is described to form oxazolidinones of (1-aminocyclopropyl)methanols with high selectivity. The site of nucleophilic attack is directed by connecting the two reaction components and by employing an electron-deficient triarylphosphine ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 26 publications
0
55
0
2
Order By: Relevance
“…[44] In jüngster Zeit hat sich der Fokus auf die Verwendung von unedlen Übergangsmetall-Katalysatoren auf Basis von Cobalt und Mangan verlagert. [48] Es wird angenommen, dass sich die zwitterionische h 3 -Allyl-Pd-Spezies in einem dynamischen Gleichgewicht mit einem h 2 -Palladacyclobutanon befindet und sowohl nukleophilen als auch elektrophilen Charakter besitzt (Schema 15). [45] Die Produkte wurden typischerweise mit moderaten E/Z-Verhältnissen von etwa 80:20 isoliert.…”
Section: Allylierung Durch C-h-aktivierung Mit Vccsunclassified
“…[44] In jüngster Zeit hat sich der Fokus auf die Verwendung von unedlen Übergangsmetall-Katalysatoren auf Basis von Cobalt und Mangan verlagert. [48] Es wird angenommen, dass sich die zwitterionische h 3 -Allyl-Pd-Spezies in einem dynamischen Gleichgewicht mit einem h 2 -Palladacyclobutanon befindet und sowohl nukleophilen als auch elektrophilen Charakter besitzt (Schema 15). [45] Die Produkte wurden typischerweise mit moderaten E/Z-Verhältnissen von etwa 80:20 isoliert.…”
Section: Allylierung Durch C-h-aktivierung Mit Vccsunclassified
“…Hayashi has exemplified the potential of 2‐alkylidenetrimethylenecarbonates for the synthesis of N‐heterocycles . Following on from their successful demonstration that the Pd‐catalyzed reaction of γ‐methylene‐δ‐valerolactones with alkylisocyanates delivered both piperidone and pyrrolidinone products (see Section “γ‐Methylidene‐δ‐valerolactones”), the authors applied the same methodology to the reaction of 2‐alkylidenetrimethylene carbonates 81 with alkylisocyanates for the synthesis of oxazolidinones (Scheme ).…”
Section: Pd‐stabilized Zwitterions Bearing An O‐centered Anionmentioning
confidence: 99%
“…Hayashi has exemplified the potentialo f2 -alkylidenetrimethylenecarbonates for the synthesis of N-heterocycles. [85] Following on from their successful demonstration that the Pd-catalyzed reactiono fg-methylene-d-valerolactones with alkylisocyanates delivered both piperidone andp yrrolidinone products (see Section" g-Methylidene-d-valerolactones"), [32] the authors applied the same methodology to the reaction of 2-alkylidenetrimethylene carbonates 81 with alkylisocyanates for the synthesis of oxazolidinones (Scheme 54). The reactionr equiredt he use of electron-deficient phosphine (4-CF 3 C 6 H 4 ) 3 P, consistent with their previouss tudies, [32] and was tolerant of aw ide range of alkylidene substituents as well as variousa lkylisocyanates.…”
Section: Pd-stabilized Zwitterions Bearing An O-centered Anion 2-alkymentioning
confidence: 99%
“…Hulshof and coworkers reported that the reaction of 1-octanol in the presence of Ru 3 (CO) 12 (5 mol %) and TTPP (17 mol %) with tolane (200 mol %) as hydrogen acceptor in p-xylene at 100 • C for 4 h gave 1-octanal in 60% yield (eq 18). 13 p-xylene 100 °C, 4 h Ru 3 (CO) 12 (5 mol %) P(4-CF 3 -C 6 H 4 ) 3 (17 mol %) Final Notes. Tris [4-(trifluoromethyl)phenyl]phosphine has been widely used as an electron-deficient phosphine ligand in the transition metal-catalyzed cross-coupling, oxidative crosscoupling, catalytic alkene functionalization, and oxidation of alcohols.…”
Section: %mentioning
confidence: 99%
“…Tris[4-(trifluoromethyl)phenyl]phosphine has been employed as a ligand for palladium-catalyzed chemo-and diastereoselective decarboxylative cyclopropanation of 2-alkylidene trimethylene carbonate with isocyanates. Shintani et al found that the reaction of 2-benzylidene trimethylene carbonate with benzyl isocyanate in the presence of PdCp(η 3 -C 3 H 5 ) (5 mol %) with TTPP (10 mol %) in dichloromethane at 40 • C for 6 h produced cyclopropanation product in 84% yield with high chemoselectivity (92%) and diastereoselectivity (96%) (eq 17) 12. …”
mentioning
confidence: 99%